Patriotism in the perspective of 20-, 40- and 60-year-olds in Podkarpacie Voivodeship - Lulek, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Patriotism is a category defining human life aimed at the common good. It depicts the emotional bond of individuals with their homeland and the sense of social and cultural bond with fellow citizens. It is based on universal values, including openness to other people, care and responsibility for the community, respect for history and national culture. The political, social and cultural changes taking place reveal new faces of love for one’s homeland, which is why there is a need to reflect on the ways of understanding patriotism. Guided by these premises, this study presents ways of defining the concept of patriotism by three successive generations of Podkarpacie residents, i.e. young adults, middle-aged people and seniors. Seven areas of understanding patriotism were taken into account – historical, territorial, cultural, ethical, emotional, economic and ecological as well as numerous categories within them. The research was carried out in the paradigm of quantitative research on a representative group.

Patriotyzm jest kategorią określającą życie człowieka ukierunkowaną na dobro wspólne. Obrazuje emocjonalną więź jednostki z ojczyną oraz poczucie więzi społecznej i kulturowej ze współobywatelami. Oparty jest na wartościach uniwersalnych, w tym otwartości na drugiego człowieka, trosce i odpowiedzialności za wspólnotę, szacunku do historii i kultury narodowej. Dokonujące się przemiany polityczne, społeczne i kulturowe odsłaniają nowe oblicza umiłowania ojczyzny, dlatego też zachodzi potrzeba refleksji nad sposobami ujmowania patriotyzmu. Kierując się tymi przesłankami, w niniejszym opracowaniu przedstawiono sposoby definiowania pojęcia „patriotyzm” przez trzy kolejne pokolenia mieszkańców Podkarpacia, to jest młodych dorosłych, osoby w wieku średnim i seniorów. Uwzględniono siedem obszarów ujmowania patriotyzmu – historyczny, terytorialny, kulturowy, etyczny, emocjonalny, ekonomiczny oraz ekologiczny, jak też liczne kategorie w ich obrębie. Badania zrealizowano w paradygmacie badań ilościowych na reprezentatywnej grupie.
Patriotyzm w perspektywie 20-, 40- i 60-latków na Podkarpaciu
Keywords: patriotism; types of patriotism; generation of 20-; 40- and 60-year-olds; Podkarpacie Voivodeship; patriotyzm; rodzaje patriotyzmu; pokolenie 20-; 40- i 60-latków; Podkarpacie